First record of the genus Soliperla (Plecoptera: Peltoperlidae) from China with description of a new species - Huo, Qing-Bo; Du, Yu-Zhou; Yuan, Dan (Zootaxa, 2017)
The genus Soliperla Ricker, 1952 has been considered endemic to western North America, is now reported from Sichuan Province of southwestern China. In this paper, we describe a new species, S. wanglanga Huo & Du, sp. nov. The new species is characterized by a large inverted trapezoid sclerite on tergum 10, a bilobed aedeagal apex, and large dark areas on the frontoclypeus in the adult male. The nymph has conspicuous pale areas on terga 4–7.